Polska Partia Robotnicza na ziemi kłodzkiej i jej droga do władzy (1945–1948) - Łagojda, Krzysztof (Komunizm: System - Ludzie - Dokumentacja, 2023)
The article discusses the issue of the origin and operation of the Polish Workers’ Party in the Kłodzko region. The author focuses on several issues related to the history of the communist party, outlining the beginnings of the party in the region, problems with establishing party committees, an influx of new members, and their motivations for joining the party. He also tries to characterise the first secretaries of district committees in Kłodzko and Bystrzyca Kłodzka, predominantly in terms of their education, social background, and connections to the pre-war communist movement. Subsequently, the author discusses how the party came to power, the way the communist party operated in the popular referendum and elections to the Legislative Sejm, the scale of repression against the Polish People’s Party, and the mass propaganda aimed at the Polish society. Lastly, the article discusses the road to the “unity” of the communist party with the Polish Socialist Party, or rather the communist activities aimed at absorbing the socialist party.